A DUAL-CHANNEL SUPPLY CHAIN MODEL OF COMPLEMENTARY PRODUCTS BY CONSIDERING GREEN MANUFACTURING LEVEL - Mulyani, Sabrina Sri; Setiyowati, Ririn; Khurdi, Nughthoh Arfawi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The development of technology and the internet has encouraged industry players to develop their businesses by adding online sales media, which previously only used offline sales media. By adding online sales media, industry players can expand their markets so they can increase profits. This study aims to modify the DCSC model for complementary products by considering the green manufacturing level to maximize the profit of a system consisting of two manufacturers and one retailer.. Based on the model that has been constructed, the optimal solution is determined so that maximum profits are obtained for each model actor in centralized scenarios. After that, the model is applied and sensitivity analysis of its parameters is carried out. Based on the research results, it appears that the policy that is more profitable for each actor in terms of system benefits is the centralized scenario. Analysis of changes in selling price elasticity values and cross price sensitivity of one of the complementary products sold in two channels influences the increase or decrease in profits of each actor and system profits. However, changes in the value of cross-price sensitivity between two complementary products indicate a decrease in the profits of each actor and the profits of the system. The change in the sensitivity value of the green manufacturing level for each product shows an increase in system profits and retailer profits, where when the sensitivity value of the green manufacturing level of product 1 is greater, the profit of manufacturer 1 is also greater, but the profit of manufacturer 2 is smaller. Conversely, when the green manufacturing level sensitivity value of product 2 becomes greater, the profit of manufacturer 2 also becomes greater, but the profit of manufacturer 1 becomes smaller.